2016
DOI: 10.1038/srep36746
|View full text |Cite
|
Sign up to set email alerts
|

High glucose upregulates BACE1-mediated Aβ production through ROS-dependent HIF-1α and LXRα/ABCA1-regulated lipid raft reorganization in SK-N-MC cells

Abstract: There is an accumulation of evidence indicating that the risk of Alzheimer’s disease is associated with diabetes mellitus, an indicator of high glucose concentrations in blood plasma. This study investigated the effect of high glucose on BACE1 expression and amyloidogenesis in vivo, and we present details of the mechanism associated with those effects. Our results, using ZLC and ZDF rat models, showed that ZDF rats have high levels of amyloid-beta (Aβ), phosphorylated tau, BACE1, and APP-C99. In vitro result w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
45
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 70 publications
(72 reference statements)
4
45
0
Order By: Relevance
“…It has been found that an upregulation of HIF‐1α enhanced expression of BACE1, while the HIF‐1α knock‐out mouse demonstrated a downregulation in BACE1 expression in hippocampus . Recently, another investigation reported that high glucose‐induced oxidative stress condition stimulated Aβ production in ZDF rats through HIF‐1α‐dependent direct expression of BACE1, indicating a close link between HIF‐1α and Aβ formation under oxidative conditions . However, whether NTP plays an important role in the regulation of HIF‐1α requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been found that an upregulation of HIF‐1α enhanced expression of BACE1, while the HIF‐1α knock‐out mouse demonstrated a downregulation in BACE1 expression in hippocampus . Recently, another investigation reported that high glucose‐induced oxidative stress condition stimulated Aβ production in ZDF rats through HIF‐1α‐dependent direct expression of BACE1, indicating a close link between HIF‐1α and Aβ formation under oxidative conditions . However, whether NTP plays an important role in the regulation of HIF‐1α requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…According to our previous study, 13 the viabilities of HT22 cells could significantly decrease when the cells were exposed to 40 μmol/L Aβ 25-35 for 24 hours. Thus, we selected 40 μmol/L as the optimal concentration of Aβ [25][26][27][28][29][30][31][32][33][34][35] for our subsequent research. HT22 cells were preconditioned with specified doses of NTP for 16 hours and subsequently treated with or without 40 μmol/L Aβ 25-35 for 24 hours.…”
Section: Cell Culture Differentiation Aβ 25-35 Preparation and Tmentioning
confidence: 99%
See 1 more Smart Citation
“…Several lines of evidence suggest that culturing cells in high glucose concentrations can alter APP processing and affect APP protein levels (Lee, et al 2016; Yang, et al 2013). Additionally, a recent study utilizing glucose clamps to sustain hyperglycemia demonstrates that increasing glucose concentrations in vivo alters APP processing to influence Aβ levels in the CSF (Macauley, et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The SK‐N‐MC and SH‐SY5Y neuroblastoma cell lines and mouse hippocampal neurons have been widely used for investigating the pathogenesis of neuronal diseases related to hyperglycemia and DM . Moreover, use of the neuronal cell lines has advantages in studies into the identification of molecular mechanism due to their high homogeneity and reproducibility.…”
Section: Introductionmentioning
confidence: 99%